Health and wellbeing in design studio briefs – Architecture and engineering graduating students' motivations and approaches. (March 2020) - Oliveira, Sonja; Griffin, Emma; Cash, Dan; Marco, Elena
Abstract: The purpose of this paper is to reflect upon architecture and environmental engineering students' approaches to health and wellbeing issues in design studio project briefs. The design studio project is a key aspect of the students' fourth year programme in a dual accredited (RIBA/ARB and CIBSE) BEng course in the SW of England. Whilst the overarching site and brief are set by the studio leader, each student develops their own project agenda drawing on extensive urban and site analysis as well as precedent research. Particular detailed aspects of the brief are then further analysed and researched as part of an engineering report study. The research draws on first author's earlier work on effects of non-prescriptive briefs on transdisciplinary studio working in architecture and engineering programmes. Drawing on visual ethnography methods, the preliminary observations drawn out of the study begin to consider key intrinsic/extrinsic motivations and assumptions students draw on to develop a health and wellbeing agenda in their projects and the way these motivations further inform analysis in the engineering reports. The implications of the research are twofold. First, the preliminary analysis enables new insights into assumptions graduating architecture and engineering students draw on to develop a health and wellbeing motivated agenda. Second the study has benefits for design studio education brief setting approaches in particular, increasingly drawn upon in engineering and multidisciplinary built environment pedagogy. Practical application : This paper enables new initial insights into ways designers (architects and building services engineers) approach health and wellbeing issues at early stages of design, drawing on a higher education empirical setting. It is particularly relevant to professionals as well as educators in the built environment.